1989
DOI: 10.1007/bf00273563
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a severity of illness score (APACHE II) in a surgical intensive care unit

Abstract: The intensive care unit is an important resource for the treatment of patients needing medical and surgical care for complicated diseases. The diversity of diseases and the difference in arrangements between hospitals providing such care have limited the precision of evaluations of intensive care. We have measured the admission characteristics and hospital mortality of 598 consecutive patients admitted to our Surgical Intensive Care Unit (SICU) using a severity of disease classification system (APACHE II) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 13 publications
3
24
0
1
Order By: Relevance
“…In comparing the capability of the APACHE II system for predicting mortality through this method, we observed that in this patient population it was meaningfully lower than what was recorded in the study by Knaus et al 7 and some from other countries, 9,13,14,19 but similar to what was recorded in other studies, 6,8,17 including one from Brazil. 20 In the 2 x 2 decision matrix assessment, the most accurate classification percentage was obtained using criterion 0.4, which correctly classified 75.2% of the patients.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…In comparing the capability of the APACHE II system for predicting mortality through this method, we observed that in this patient population it was meaningfully lower than what was recorded in the study by Knaus et al 7 and some from other countries, 9,13,14,19 but similar to what was recorded in other studies, 6,8,17 including one from Brazil. 20 In the 2 x 2 decision matrix assessment, the most accurate classification percentage was obtained using criterion 0.4, which correctly classified 75.2% of the patients.…”
supporting
confidence: 72%
“…The ability of this gradational system to predict mortality rates for different patient groups has been assessed in several countries. 8,9,[12][13][14][17][18][19] The following items have been used for assessing the predictive capability of the APACHE II index: receiver operating characteristic curve, 2 x 2 decision matrix, and linear regression analysis (calibration curve).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the calculation of this index requires at least two measurements of each physiological parameter and the second of these will be influenced by the intensive treatment. 30 Another obstacle is the subjectivity inherent in certain items on the worker's data sheets. The more researchers who apply this index, the less precise are the data.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Our objective was to determine, in a large number of patients, if echocardiographic data would add prognostication to existing clinical variables in MSICU patients. This clinical study attempts to associate specific cardiovascular pathology identified utilizing TTE with mortality in the MSICU.…”
Section: Objectifmentioning
confidence: 99%